Storytelling, Seafaring, and Travel Writing : The Persian Gulf and the Indian Ocean - Alshaar, Nuha; Sala, Beate Ulrike La; Wilmsen, David (Islamic History and Civilization, 2026)
Storytelling, Seafaring, and Travel Writing advances research on Islamic travel writing, with a particular concentration on the Persian Gulf and Indian Ocean. Ranging from the late antiquity to the present, this collection explores how storytelling, travelogues, and seafaring narratives have contributed to cultural discourses and intellectual traditions. By examining Arab seafaring and travel from new angles and through cross-cultural and interdisciplinary lenses, these essays challenge conventional interpretation. Essential for scholars and researchers in Islamic studies, philosophy, literary analysis, and cultural history, it illustrates how real and imagined narratives have profoundly influenced cross-cultural exchanges and the construction of moral and cultural paradigms over time.